2021
DOI: 10.3390/catal11050563
|View full text |Cite
|
Sign up to set email alerts
|

Dry Reforming of Methane over Carbon Fibre-Supported CeZrO2, Ni-CeZrO2, Pt-CeZrO2 and Pt-Ni-CeZrO2 Catalysts

Abstract: Dry reforming of methane (DRM) is one of the most important processes allowing transformation of two most potent greenhouse gases into a synthesis gas. The CH4 and CO2 are converted at high temperatures in the presence of a metal catalyst (usually Ni, also promoted with noble metals, supported over various oxides). The DRM process is not widely used in the gas processing industry because of prompt deactivation of the catalyst owing to carbon deposition and the blockage of the metal active sites. This problem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 85 publications
1
1
0
Order By: Relevance
“…This produces PtO and an increase in the concentration of the metal oxide(s) ions, which are the active sites for CO 2 reduction. 44 The PtO was detected by XRD (Fig. 1), which was proven by previous research.…”
Section: Resultssupporting
confidence: 77%
“…This produces PtO and an increase in the concentration of the metal oxide(s) ions, which are the active sites for CO 2 reduction. 44 The PtO was detected by XRD (Fig. 1), which was proven by previous research.…”
Section: Resultssupporting
confidence: 77%
“…1 wt%) with high dispersion NM-catalysts are designed and used [6,50]. Among the noble metals, Rh and Pt have been mostly investigated so far under DRM conditions [51][52][53][54][55][56][57][58][59][60][61], while few studies have been reported for Ru [62][63][64][65] and, especially, Ir [50]. A similar trend is apparent for studies concerning bimetallic NM-Ni based catalysts [1].…”
Section: Introductionmentioning
confidence: 78%